Aqueous alteration mapping in Rishabdev ultramafic complex using imaging spectroscopy - Hrishikesh Kumar; A.S. Rajawat (International Journal of Applied Earth Observations and Geoinformation, 2020)
Hyperspectral remote sensing/imaging spectroscopy has enabled precise identification and mapping of hydrothermal alteration mineral assemblages based on diagnostic absorption features of minerals. In the present study, we use Airborne Visible InfraRed Imaging Spectrometer-Next Generation (AVIRIS-NG) datasets acquired over Rishabdev ultramafic suite to derive surficial mineral map using least square based spectral shape matching in wavelength range of diagnostic absorption features of minerals. Resulting mineral map revealed presence of hydrothermally altered serpentine group of minerals and associated alteration products (talc and dolomite) along with clays and phyllosilicates. Mineral maps are validated using field spectral measurements and published geological map. Involvement of low temperature (<350 °C) hydrothermal fluid in serpentinization of ultramafic rocks in the region is inferred from analysis of deepest absorption features of muscovites at 2.20 μm, spectral abundance of lizardite and absence of prenhite-pumpyllite facies mineral assemblages. Talc was found to be the most common alteration product of serpentines followed by dolomites. Intense alteration of serpentines to talc along the fracture zone is attributed to the circulation of carbon dioxide rich hydrothermal fluids along these conduits. Kaolinite and halloysite are primarily associated with granites and are the result of hydrothermal alteration of plagioclase feldspar in granites while muscovite and illites are generally associated with phyllites and quartzites . The study demonstrates the potential of imaging spectroscopy for mapping hydrothermal alteration mineral assemblages in ultramafic complex.